Evaluation of the Dracocephalum ruyschiana L. and Salvia sclarea seed material cryopreservation effectiveness - Dodonova, A.Sh.; Pavlov, A.V.; Oreshkin, N.D.; Nortseva, M.A.; Kyzdarova, D.K. (Fundamental and Experimental Biology, 2024)
Cryopreservation of plant material of valuable plants is an effective way to preserve biological diversity in conditions of active and widespread anthropogenic pressure on natural ecosystems. Introduction to cryocollections is justified not only for food agricultural plants, but also for medicinal plants that have valuable secondary metabolites and essential oils. These include Dracocephalum ruyschian and Salvia sclarea. To effectively restore the viability of seeds after freezing in liquid nitrogen, we examined the influence of various cryoprotectants: glycerin, dimethyl sulfoxide and polyvinypyrrolidone, as well as various methods of their application — at room temperature and in the cold. It was found that for effective cryopreservation of Dracocephalum ruyschiana seed material, the use of cryoprotectors is justified; however, the method of their application does not matter. When cryopreserving Salvia sclarea seed material, it is important to use cryoprotectors and introduce them into the cooling system, preferably at the crystallization temperature of water; in this case, the energy of seed germination increases significantly.